2011
DOI: 10.1007/s00702-011-0724-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and distribution of salsolinol-like compound, 1-acetyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline (ADTIQ) in Parkinsonian brains

Abstract: Parkinson's disease (PD) arises from the loss of dopaminergic neurons in the substantia nigra. 1-Methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) is well known to cause Parkinsonism in humans with neurotoxicity specific for dopaminergic neurons. The experience with MPTP supports the hypothesis that endogenous or xenobiotic neurotoxins are involved in the pathogenesis of PD in humans. In our study, 1-acetyl-6, 7-dihydroxy-1, 2, 3, 4-tetrahydro-isoquinoline (ADTIQ), a novel compound, was found in frozen huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…In vivo study, HPLC-ESI-MS/MS results showed that the concentration of ADTIQ was 63.6 ± 4.6 fM/mg wet tissue in the substantia nigra of rat [73]. In putamen of PD patients, the level of ADTIQ was higher than that in controls, which suggested that this novel compound might be related to PD [15]. And ADTIQ is endogenously synthesized from the condensation of dopamine and methylglyoxal (MGO).…”
Section: Adtiq Is a Link Between Pd And Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo study, HPLC-ESI-MS/MS results showed that the concentration of ADTIQ was 63.6 ± 4.6 fM/mg wet tissue in the substantia nigra of rat [73]. In putamen of PD patients, the level of ADTIQ was higher than that in controls, which suggested that this novel compound might be related to PD [15]. And ADTIQ is endogenously synthesized from the condensation of dopamine and methylglyoxal (MGO).…”
Section: Adtiq Is a Link Between Pd And Diabetesmentioning
confidence: 99%
“…CTIQs and their derivatives can be synthesized based on different active aldehydic derivatives and DA product or its metabolites, such as 1-methyl-6,7-dihydroxyl-1,2,3,4-tetrahydroisoquinoline(Sasolinol,Sal),1-acetyl-6,7-dihydroxyl-1,2,3,4-tetrahydroisoqu-inoline (ADTIQ) and 6,7-dihydroxyl-1,2,3,4-tetrahydro-isoquinoline (norsalsolinol,norsal) [12,15,16]. These CTIQs listed above could be reacted into N-methylnorsalsolinol (NM-NorSal), N-methylsalsolinol (NM-Sal) and N-methyl-ADTIQ (NM-ADTIQ) by nitrogen methyltransferase respectively, and then generated to ion [17].…”
Section: Endogenous Catechol Tetrahydroisoquinolinesmentioning
confidence: 99%
“…Not only can MG directly damage mitochondria [65,66] and may be associated with age-related cognitive decline [67], but the bicarbonyl can also react with dopamine [68,69] to form 1-acetyl-6,7-dihydroxy-1,2,3,4-tetrahydro-isoquinaline (ADTIQ), which is a salsolinol-like compound [69]. ADTIQ not only accumulates in PD brains but also mimics the effects of MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) whose effects on mitochondria resemble the changes associated with PD [69].…”
Section: Methylglyoxal and Pdmentioning
confidence: 99%
“…ADTIQ not only accumulates in PD brains but also mimics the effects of MPTP (1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine) whose effects on mitochondria resemble the changes associated with PD [69]. Further evidence supporting the proposed link between MG, dopamine and generation of the neurotoxin ADTIQ is shown by the increased levels of glycolytic enzymes, MG and ADTIQ in the brains of diabetic rats [70].…”
Section: Methylglyoxal and Pdmentioning
confidence: 99%
“…A recent investigation found that methylglyoxal mediated modification of the Na v 1.8 sodium channel is associated with hyperalgesia in diabetic neuropathy [173], implicating a direct role for methylglyoxal in diabetes-induced nociceptive pain. In addition, a novel neurotoxin known as ADTIQ (1-acetyl-6,7-dihydroxy-1,2,3,4-tetrahydroisoquinoline) discovered in the brains of PD patients has been found to be the result of methylglyoxal reacting with dopamine [174]. It has been suggested that this neurotoxin, the result of altered bioenergetic homeostasis and a specific neurotransmitter, might be a common pathogen between Parkinson’s disease and diabetes.…”
Section: Alzheimer’s Disease Parkinson’s Disease and Diabetic Neuromentioning
confidence: 99%